Revitalization of the Workforce Training System in Response to the Dynamics of Globalization: A Systematic Literature Review - Utami, Dian Sri; Prakosa, Hilman; Lataruva, Eisha; Hidayati, Retno (LifeSciFi, 2024)
The global landscape of workforce training has been profoundly influenced by the forces of globalization, digital transformation, and the rapid evolution of job requirements. This paper presents a systematic literature review on the transformation of workforce training in the face of globalization's challenges and opportunities. By examining a wide range of scholarly sources, this study aims to identify emerging trends, prevailing challenges, and potential frameworks for effective workforce development. Findings indicate a growing emphasis on digital skills, adaptability, and lifelong learning, alongside the need for a comprehensive approach that addresses disparities in training accessibility. This review contributes insights into the critical elements for developing workforce training strategies that are globally competitive, inclusive, and resilient.